Pore Structure and Morphology Characterizations of Mesoporous ZSM-5 Synthesized at Various Aging Time - Djoko Hartanto; Tri Esti Purbaningtias; Hamzah Fansuri; Didik Prasetyoko (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
Mesoporous ZSM-5 has been successfully synthesized at various aging time of 6, 12 and 24 h. Mesoporous ZSM-5 was synthesized using cetyltrimethylammonium bromide (CTABr) as a template. Synthesis was carried out hydrothermally with aging and crystallization temperature at 60oC and 150oC. XRD patterns of the resulted material showed diffraction lines at 2θ = 23o and at small angle (2θ < 5o) which is characteristic of the structure of ZSM-5 and the existing of the mesoporous material. It was found that crystallinity of the sample increased at longer aging time. The result of nitrogen gas sorption analysis showed that all samples have pore size about 3,8 nm. The porosity of ZSM-5 decreased with shorter of aging time. ZSM-5 synthesized at 6 h aging time has the highest porosity of 72.57%. Aging time also affected the particle size, the longer the aging time, the smaller the particle size. The particle size was ranging 1.25 – 1.0 μm.